2015
DOI: 10.11648/j.ijsqa.20150102.11
|View full text |Cite
|
Sign up to set email alerts
|

The Qualities of Albanian Soft Wheat Genotypes – the Mathematical Approach

Abstract: The purpose of this study was to evaluate some of the soft wheat genotypes cultivated in Albania, concerning the technological and rheological characteristics of the produced dough, in regard to further cultivation. The obtained results for the soft lines of wheat collected during the summer seasons of 2013 and 2014 showed high contents of protein (13.36%-17.42%), also strong water absorption capacity (59.70%-67.40%) with high values of Mixolab parameter C2 (0.24Nm-0.54Nm), thus predicting good protein quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The Mixolab provides information about protein and starch behavior and enzyme actions (Bosc‐Bierne, Brun, & Dubat, ). A low C2 value or high C2‐C1 difference in the Mixolab indicates weak‐dough gluten strength (Laze et al, ; Öztürk, Kahraman, Tiftik, & Köksel, ). A study done with selected soft wheat genotypes showed that high Mixolab C2 values inversely correlated with cookie‐spread ratio, and Mixolab stability was negatively associated with biscuit sensory score (Karaduman, ; Karaduman & Ercan, ).…”
Section: Resultsmentioning
confidence: 99%
“…The Mixolab provides information about protein and starch behavior and enzyme actions (Bosc‐Bierne, Brun, & Dubat, ). A low C2 value or high C2‐C1 difference in the Mixolab indicates weak‐dough gluten strength (Laze et al, ; Öztürk, Kahraman, Tiftik, & Köksel, ). A study done with selected soft wheat genotypes showed that high Mixolab C2 values inversely correlated with cookie‐spread ratio, and Mixolab stability was negatively associated with biscuit sensory score (Karaduman, ; Karaduman & Ercan, ).…”
Section: Resultsmentioning
confidence: 99%